Laboratory diagnosis of COVID-19 - Ekaterini S. Goudouris (Elsevier, 2021)
Objectives: This was a non-systematic review of the literature on the laboratory diagnosis of COVID-19. Data sources: Searches in PubMed and Google Scholar for articles made available in 2020, using the terms "diagnosis" OR "diagnostic" OR "diagnostic tests" OR "tests" AND "COVID-19" OR "SARS-CoV-2" in the title. Summary of findings: Tests for the etiological agent identify genetic material of SARS-CoV-2 or humoral responses to it. The gold standard for diagnosis is the identification of viral genome targets by real-time polymerase chain reaction (RT-PCR) in respiratory tract materials during the first week of symptoms. Serological tests should be indicated from the second week of symptoms onwards. A wide range of different tests is available, with variable sensitivity and specificity, most of which require validation. Laboratory tests such as complete blood count, C-reactive protein (CRP), D-dimer, clotting tests, lactic dehydrogenase (LDH), ferritin, and procalcitonin identify risk of disease with greater severity, thromboembolic complications, myocardial damage, and/or worse prognosis. Imaging tests may be useful for diagnosis, especially when there is a compatible clinical picture, and other tests presented negative results or were unavailable. Conclusions: The identification of genetic material of the virus by RT-PCR is the gold standard test, but its sensitivity is not satisfactory. The diagnosis of COVID-19 should be based on clinical data, epidemiological history, tests for etiological diagnosis, and tests to support the diagnosis of the disease and/or its complications. New diagnostic methods with higher sensitivity and specificity, as well as faster results, are necessary.